(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2022)
The purpose of this paper is to provide insight into the individual and structural causes of ethnic cleansing. The paper argues that the cause of ethnic cleansing is cultural or ethnic racism, and that the structural conditions under which ethnic cleansing occurs in society are modern models of social organization such as democracy and nationalism, which form the context in which interethnic prejudice is unleashed in its full strength. The root of this prejudice, in multicultural post-communist states, is usually a very common form of primordial ethnic loyalties, which, by their irrational and antagonistic nature, in periods of early democratic consolidation of society, almost instantly generate irreconcilable demands and feelings of threat from other ethnicities, causing the conflicts between communities that historically share the same territory.